TCWG on Cost of Equity with Audit Opinion as a Moderating Variable - Endarty, Kharisma; Apandi, Nelly Nur; Widarsono, Agus (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2025)
This study examines the impact of the audit committee (AC) on the cost of equity (COE), with audit opinion (AO) as a moderating variable, in hotel and property sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Using a quantitative approach with panel data regression, the findings indicate that the number of audit committee members does not significantly affect COE. Furthermore, audit opinion fails to strengthen the relationship between the audit committee and COE, suggesting that investors do not fully consider these factors when assessing risks and expected returns. These results highlight the need for improving the quality and effectiveness of audit committees in overseeing financial reporting processes to enhance transparency and investor confidence. Additionally, firms should ensure that their financial statements reflect accurate and reliable information to mitigate investment risks. The study contributes to the literature on corporate governance by providing empirical evidence on the limited role of audit committees and audit opinions in influencing the cost of equity. From a practical perspective, regulators and corporate decision-makers should emphasize strengthening governance mechanisms beyond mere compliance with regulatory requirements. Enhancing financial disclosures and reinforcing the credibility of audit committees may help reduce perceived risks among investors, leading to lower capital costs. This study underscores the importance of transparency in financial reporting and the role of governance structures in shaping investor perceptions. Future research should explore other governance attributes, such as board independence and financial expertise, in influencing COE to provide a more comprehensive understanding of the determinants of equity financing costs.